Bone Tumours (IntechOpen, 2023)
Bone tumour management is a rapidly evolving field, thanks to ongoing successful research. This book is a comprehensive review of selected topics that have seen rapid change over the last decade. Arranged in an easy-read format, it contains three sections: the first discusses general topics pertaining to bone tumours; the second is devoted to breast carcinoma; and a larger final section concerns sarcomas and their management. This book explains complex topics in an easy-to-understand format, elegantly presented by a group of eminent researchers. It is a must-have book for researchers, scientists and clinicians, including medical students, oncologists, orthopaedic surgeons, and anyone who manages bone tumours. The book may serve as a CME (continuing medical education) tool for those wishing to update their knowledge on bone tumours.